Enforcing Extended Porphyrin J-Aggregate Stacking in Covalent Organic Frameworks. - Keller, Niklas; Calik, Mona; Sharapa, Dmitry; Soni, Himadriben; Zehetmaier, Peter M.; Rager, Sabrina; Auras, Florian; Jakowetz, Andreas C.; Görling, Andreas; Clark, Timothy; Bein, Thomas (Journal of the American Chemical Society, 2018)
The potential of covalent organic frameworks (COFs) for realizing porous, crystalline networks with tailored combinations of functional building blocks has attracted considerable scientific interest in the fields of gas storage, photocatalysis, and optoelectronics. Porphyrins are widely studied in biology and chemistry and constitute promising building blocks in the field of electroactive materials, but they reveal challenges regarding crystalline packing when introduced into COF structures due to their nonplanar configuration and strong electrostatic interactions between the heterocyclic porphyrin centers. A series of porphyrin-containing imine-linked COFs with linear bridges derived from terephthalaldehyde, 2,5-dimethoxybenzene-1,4-dicarboxaldehyde, 4,4'-biphenyldicarboxaldehyde and thieno[3,2- b]thiophene-2,5-dicarboxaldehyde, were synthesized, and their structural and optical properties were examined. By combining X-ray diffraction analysis with density-functional theory (DFT) calculations on multiple length scales, we were able to elucidate the crystal structure of the newly synthesized porphyrin-based COF containing thieno[3,2- b]thiophene-2,5-dicarboxaldehyde as linear bridge. Upon COF crystallization, the porphyrin nodes lose their 4-fold rotational symmetry, leading to the formation of extended slipped J-aggregate stacks. Steady-state and time-resolved optical spectroscopy techniques confirm the realization of the first porphyrin J-aggregates on a > 50 nm length scale with strongly red-shifted Q-bands and increased absorption strength. Using the COF as a structural template, we were thus able to force the porphyrins into a covalently embedded J-aggregate arrangement. This approach could be transferred to other chromophores; hence, these COFs are promising model systems for applications in photocatalysis and solar light harvesting, as well as for potential applications in medicine and biology.

Fractal-seaweeds type functionalization of graphene - Amsharov, Konstantin; Sharapa, Dmitry I.; Vasilyev, Oleg A.; Martin, Oliver; Hauke, Frank; Görling, Andreas; Soni, Himadriben; Hirsch, Andreas (Carbon, 2020)
In this work, we present a systematic investigation on the regioselectivity and topicity of radical hydrogenation/alkylation of graphene. The complex process of sequential covalent binding of hydrogen and methyl radicals to the edges and basal plane of graphene, and addition to the direct neighborhood of pre-existing defects were quantitatively investigated using different computational techniques. Considering both thermodynamic and kinetic factors a general model for graphene functionalization has been developed. Based on the proposed model we performed numerical Monte-Carlo simulations, which provide evidence of a fractal expansion of functionalized regions leading to a fractal-seaweeds type of addition. We show that the applications of the model is widespread and includes the description of Birch-like hydrogenation, reductive alkylation and direct radical addition, which allows to evaluate the effect of the size, shape and the quality of a graphene flake on the addition morphology.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Functionalization regioselectiviy; Graphene; Topicity

Metalated Graphyne-Based Networks as Two-Dimensional Materials: Crystallization, Topological Defects, Delocalized Electronic States, and Site-Specific Doping - Yang, Zechao; Sander, Tim; Gebhardt, Julian; Schaub, Tobias A.; Schonamsgruber, Jorg; Soni, Himadriben; Görling, Andreas; Kivala, Milan; Maier, Sabine (ACS nano, 2020)
Graphyne-based two-dimensional (2D) carbon allotropes feature extraordinary physical properties; however, their synthesis as crystalline single-layered materials has remained challenging. We report on the fabrication of large- area organometallic Ag-bis-acetylide networks and their structural and electronic properties on Ag(111) using low-temperature scanning tunneling microscopy combined with density functional theory (DFT) calculations. The metalated graphyne-based networks are robust at room temperature and assembled in a bottom-up approach via surface-assisted dehalogenative homocoupling of terminal alkynyl bromides. Large-area networks of several hundred nanometers with topological defects at domain boundaries are obtained due to the Ag-acetylide bonds' reversible nature. The thermodynamically controlled growth mechanism is explained through the direct observation of intermediates, which differ on Ag(111) and Au(111). Scanning tunneling spectroscopy resolved unoccupied states delocalized across the network. The energy of these states can be shifted locally by the attachment of a different number of Br atoms within the network. DFT revealed that free-standing metal-bis-acetylide networks are semimetals with a linear band dispersion around several high-symmetry points, which suggest the presence of Weyl points. These results demonstrate that the organometallic Ag-bis-acetylide networks feature the typical 2D material properties, which make them of great interest for fundamental studies and electronic materials in devices.
CRIS-Team WoS Importer:2021-01-22

Oxygen Functionalization of Hexagonal Boron Nitride on Ni(111) - Späth, Florian; Soni, Himadriben; Steinhauer, Johann; Düll, Fabian; Bauer, Udo; Bachmann, Phillip; Hieringer, Wolfgang; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2019)
The interaction of single-layer hexagonal boron nitride (h-BN) on Ni(111) with molecular oxygen from a supersonic molecular beam led to a covalently bonded molecular oxygen species, which was identified as being between a superoxide and a peroxide. This is a rare example of an activated adsorption process leading to a molecular adsorbate. The amount of oxygen functionalization depended on the kinetic energy of the molecular beam. For a kinetic energy of 0.7 eV, an oxygen coverage of 0.4 ML was found. Near-edge X-ray adsorption fine structure (NEXAFS) spectroscopy revealed a stronger bond of h-BN to the Ni(111) substrate in the presence of the covalently bound oxygen species. Oxygen adsorption also led to a shift of the valence bands to lower binding energies. Subsequent temperature-programmed X-ray photoelectron spectroscopy revealed that the oxygen boron bonds are stable up to approximately 580 K, when desorption, and simultaneously, etching of h-BN set in. The experimental results were substantiated by density functional theory calculations, which provided insight to the adsorption geometry, the adsorption energy and the reaction pathway.
CRIS-Team Scopus Importer:2019-06-21
Keywords: adsorption; boron nitride; density functional theory; oxygen functionalization; photoelectron spectroscopy

Precise determination of graphene functionalization by in situ Raman spectroscopy - Vecera, Philipp; Chacón-Torres, Julio C.; Pichler, Thomas; Reich, Stephanie; Soni, Himadriben; Görling, Andreas; Edelthalhammer, Konstantin; Peterlik, Herwig; Hauke, Frank; Hirsch, Andreas (Nature Communications, 2017)

Reactivity of Substrate-Supported Graphene: A Case Study of Hydrogenation - Soni, Himadriben; Gebhardt, Julian; Görling, Andreas (Journal of Physical Chemistry C, 2018)

Retraction Note: Precise determination of graphene functionalization by in situ Raman spectroscopy - Vecera, Philipp; Chacón-Torres, Julio C.; Pichler, Thomas; Reich, Stephanie; Soni, Himadriben; Görling, Andreas; Edelthalhammer, Konstantin; Peterlik, Herwig; Hauke, Frank; Hirsch, Andreas (Nature Communications, 2022)
CRIS-Team Scopus Importer:2022-11-18

Triethynylmethanol Derivatives: Stable Acetylenic Building Blocks for Surface Chemistry - Prenzel, Dominik; Sander, Tim; Gebhardt, Julian; Soni, Himadriben; Hampel, Frank; Görling, Andreas; Maier, Sabine; Tykwinski, Rik (Chemistry - A European Journal, 2017)
The synthesis of non-conjugated, carbon-rich building blocks is described, based on a basic scaffold of triethynylmethanol (TEtM). The substitution of the ethynyl groups can be easily varied (including R3Si, H, Br), and this allows structural tuning for stabilization, synthetic derivatization, and adsorption on Ag(111) or Au(111). X-ray crystallography helps to explain the surprising stability of the selected derivatives in the solid state, and an unusual form of hydrogen bonding is identified from these analyses. Preliminary efforts to achieve surface-based reactions on Ag(111) and Au(111) are outlined experimentally and computationally.
Keywords: alkynes; carbon allotropes; graphdiyne; graphyne; surface chemistry

Two-dimensional delocalized states in organometallic bis-acetylide networks on Ag(111) - Yang, Zechao; Gebhardt, Julian; Schaub, Tobias; Sander, Tim; Schönamsgruber, Jörg; Soni, Himadriben; Görling, Andreas; Kivala, Milan; Maier, Sabine (Nanoscale, 2018)